Utilization of Technology in the Implementation of Pastoral Supervision in the Church - Erlina Waruwu; Andar Gunawan Pasaribu; Rosmey Meriaty br. Sormon (Tinta Emas Institute, 2025)
This article discusses how the use of digital technology can enhance the effectiveness of pastoral supervision within the church, particularly in the context of modern pastoral ministry. As the digital era continues to evolve, the need for an adaptive approach to shepherding has become increasingly urgent. Traditional methods of pastoral supervision are now shifting toward digital engagement through platforms such as WhatsApp, Zoom, Google Meet, and other online communication tools. This study employs a qualitative method with a literature review and interview approach, aiming to explore a deeper understanding of technology-based pastoral supervision practices in today’s church context. Data was collected through the review of relevant literature and supported by interviews with pastors from various regions. This approach enables the researcher to analyze the phenomenon holistically and contextually, taking into account the dynamics of ministry as well as the geographical and digital challenges faced by the church. The findings indicate that technology serves not merely as a technical tool but holds transformational potential in nurturing and supervising the spiritual growth of congregants. These insights are reinforced by the experiences of pastors who have successfully integrated digital media into their ministry practices in creative and contextual ways. This article offers an innovative contribution in the form of a proposed model for technology-based pastoral supervision that remains grounded in spiritual values, pastoral intimacy, and relevance to contemporary developments. The approach demonstrates that when used wisely, technology can strengthen ministry without diminishing the spiritual connection between pastors and their congregations.